Intensified Antituberculosis Therapy Regimen Containing Higher Dose Rifampin for Tuberculous Meningitis: A Systematic Review and Meta-Analysis - Zhang, Mengmeng; Wang, Minggui; He, Jian-Qing (Frontiers in Medicine, 2022)
Background Tuberculous Meningitis is difficult to diagnose and associated with high mortality. Recently, several studies evaluated the intensified regimen containing higher dose rifampin to treat the tuberculous meningitis. However, this topic remained to be concluded. Therefore, this systematic review and meta-analysis was conducted to evaluate pharmacokinetics parameters, safety and survival benefit of high dose rifampin for tuberculous meningitis. Method Data was searched from PubMed, EMBASE, The Cochrane Library, Web of Science for studies describe antituberculosis regimen include higher-dose of rifampin for patients with tuberculous meningitis. The quality of eligible studies was evaluated via The Cochrane Risk of Bias Tools. The meta-analysis was performed by Review Manager 5. 3 software, the synthesis of the data was shown in mean difference (MD) or relative risk (RR), and 95% confidence intervals (CIs). Results There were six randomized control trails included in this meta-analysis. The results showed that the concentration in plasma and CSF were significantly higher in the intervention group than the standard group (MD=22.08, 95%CI(16.24,27.92),p<0.00001;MD=0.74, 95%CI (0.42,1.05), p<0.00001), as well as the area under the time concentration curve between 0 and 24 hours (AUC0–24) of rifampin(MD 203.56, 95%CI (153.07,254.05), p<0.00001)in plasma, but the overall survival didn’t improved (RR=0.92, 95%CI (0.67,1.26), p=0.61).For adverse events, the results showed a statistically significant lower incidence of hypersensitivity compared with the intervention group (RR=1.72, 95%CI (1.13,2.62), p=0.01).Fortunately, other common adverse drug reactions such as liver injury, neurological events, myelosuppression, cardiotoxicity have no significant increase occurred.(RR=0.98,95%CI (0.77,1.26), p=0.90; RR=1.10,95%CI (0.94,1.30), p=0.23; RR=0.82,95%CI (0.59,1.13), p=0.22; RR=1.11,95%CI (0.66,1.86),p=0.70). Conclusion This meta-analysis suggested that the intensified treatment regimen including higher dose of rifampin significantly increased the rifampin concentration both in the plasma and CSF, and it was safe in patient with tuberculous meningitis, but had no improvement in survival rates.